016 Retirement of Performance Measures In A National Pay for Performance (P4P) Scheme. (15th August 2013) - Sutcliffe, D; Hobbs, L; Flatt, G; Shaw, E; Stokes, T; Baillie, N
Abstract : Background: P4P schemes, providing financial incentives across a range of improvement indicators, are widely used and can improve health outcomes. These systems can work at different levels, including at the national level. It is important that performance measures (PMs) used in such systems have a robust and up-to-date evidence base to support continued use and they remain fit for purpose; this involves selecting PMs for 'retirement'. Objectives: To: i) describe methods used in selecting PMs for retirement, ii) present alternative methods for selecting PMs for retirement. Methods: Identifying PMs for retirement have been based on several methods including: i) reported trends in achievement and exception reporting ii) review of paired PMs iii) review of supporting evidence and/or technical specifications iv) modified Delphi. Results: We will present results of using these methods, and discuss alternatives to these (e.g., the Nominal Group Technique), and implications for retirement of PMs. Discussion: These methods have been successful in identifying indicators for retirement. To ensure continual improvements in quality of care delivered through the P4P scheme and provide opportunities for new areas to be added, the review and retirement of PMs remains important. Implications for Guideline Developers/Users: Guideline developers should be aware of key PMs based on guidance recommendations and have systems to ensure that underpinning evidence is up-to-date. PM developers should have processes to ensure that PMs are based on up-to-date evidence and remain fit for purpose.